Examination of Knowledge and Fear Levels of Breast Cancer With the Spiritual Characteristics of Nurses - Cal, Ayse; Kabatas Yildiz, Mukerrem; Aydin Avci, Ilknur (Frontiers in Public Health, 2018)
Introduction: Breast cancer is a common problem and important to understand the beliefs that tend to increase awareness of breast cancer and to guide early diagnosis behaviors. This research is planned to designate the Examination of Knowledge and Fear Levels of Breast Cancer with the Spiritual Characteristics of Nurses. Methods: This is a descriptive type research. The universe of the research consists of woman nurses working in … Training and Research Hospital. Sampling was not preferred and 327 nurses who were on duty between January-May of 2016 and embraced to participate in research were incorporated to study. Data was collected by use of the survey form, “Breast Cancer Fear Scale” and “Comprehensive Breast Cancer Knowledge Test (GKMBT)”. Data were analyzed with SPSS 21. Software. Results: Nurses who participated in the research have an average of age of 32.27±1.04, 60.6% of which is married and have an average operation time of 12.49±9.92. Nurses' breast cancer fear level point average was 26.11±6.58, GMKBT scale general information sub-dimension point average was 7.20±2.81, treatability sub-dimension point average was 5.80±1.68 and total point average was found out to be 12.87±2.81. It was determined that nurses' knowledge levels of breast cancer and their breast cancer were not related to fear levels. Conclusion: It was concluded that the nurses' breast cancer fear level was high and their knowledge level was moderate. In line with the results obtained, it might be recommended that studies should be made to increase the nurses' knowledge and awareness on breast cancer.